PROJECT BASED LEARNING WITH PEER INSTRUCTION FLIPPED CLASSROOM DESIGN TO IMPROVE CRITICAL THINKING SKILLS AND SCIENCE LITERACY - Wilyati Agustina; Siti Naphiah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The 21st century is a globalization era in which humans are required to have 21st-century skills, including critical thinking skills and scientific literacy in order to solve problems and make the right decisions. Both skills must be prepared, including biology education students. Several research reports have shown low levels of both skills in biology students. The solution that can overcome these problems is to apply learning following the demands of the 21st century, student-centered collaboration. This study aims to analyze the effect of Project-Based Learning with the Peer Instruction Flipped Type Flipped Classroom design on critical thinking skills and scientific literacy. The subjects of this research were Biology Education students of IKIP Budi Utomo Malang. There were two classes: Class A, which implemented project-based learning with the design of the Flipped Classroom, Peer Instruction Flipped, Experiment, and Class B, which applied the Flipped Classroom with the Peer Instruction Flipped Type. The research instrument was in the form of pretest-posttest questions, critical thinking skills, and scientific literacy. Data analysis of the total value of each strategy using paired t-test. The results showed that the Flipped Classroom Peer Instruction Flipped Type in improving thinking skills and scientific literacy.